Morphology and genetics of pyloric gland adenomas in familial adenomatous polyposis - Hackeng, Wenzel M. (Histopathology, 2016)
BACKGROUND: Gastric pyloric gland adenomas (PGAs) are rare epithelial polyps that are more commonly found in autoimmune atrophic gastritis and familial adenomatous polyposis. Little is known about the morphology and genetics of PGAs in familial adenomatous polyposis. AIMS: PGAs in familial adenomatous polyposis are studied morphologically and genetically. Findings in FAP associated PGAs are compared to sporadic PGAs and related lesions such as oxyntic gland adenoma (OGA) to increase our understanding of these rare polyps. METHODS: 7 PGAs and 18 FGPs from FAP patients were collected. KRAS and GNAS mutations we determined in 6 PGAs and 18 FGPs. Immunohistochemistry was applied on 5 PGAs to provide further confirmation of the histologic subtypes and genetic alterations. Morphology of all PGAs was studied and compared to literature on sporadic PGAs and related lesions. RESULTS: All successfully sequenced PGAs (6/6) carried a GNAS mutations and half of the successfully sequenced PGAs carried a KRAS mutation (3/6). Nuclear β-catenin was only seen in one PGS with focal high-grade dysplasia. Morphologically, PGAs in FAP showed overlapping features with OGA. CONCLUSION: FAP associated PGAs have a similar genetic background, i.e. KRAS and GNAS mutation. Based on morphological findings in FAP associated PGAs it is hypothesized that PGAs and OGAs are closely related lesions.